Conserved sequence in the aggrecan interglobular domain modulates cleavage by ADAMTS-4 and ADAMTS-5 - Miwa, Hazuki E.; Gerken, Thomas A.; Huynh, Tru D.; Duesler, Lori R.; Cotter, Meghan; Hering, Thomas M. (Biochimica et biophysica acta, 2009)
Cleavage of aggrecan by ADAMTS proteinases at specific sites within highly conserved regions may be important to normal physiological enzyme functions, as well as pathological degradation. To examine ADAMTS selectivity, we assayed ADAMTS-4 and -5 cleavage of recombinant bovine aggrecan mutated at amino acids N-terminal or C-terminal to the interglobular domain cleavage site. Mutations of conserved amino acids from P18 to P12 to increase hydrophilicity resulted in ADAMTS-4 cleavage inhibition. Mutation of Thr, but not Asn within the conserved N-glycosylation motif Asn-Ile-Thr from P6 to P4 enhanced cleavage. Mutation of conserved Thr residues from P22 to P17 to increase hydrophobicity enhanced ADAMTS-4 cleavage. A P4′ Ser377Gln mutant inhibited cleavage by ADAMTS-4 and -5, while a neutral Ser377Ala mutant and species mimicking mutants Ser377Thr, Ser377Asn, and Arg375Leu were cleaved normally by ADAMTS-4. The Ser377Thr mutant, however, was resistant to cleavage by ADAMTS-5. We have identified multiple conserved amino acids within regions N- and C-terminal to the site of scission that may influence enzyme–substrate recognition, and may interact with exosites on ADAMTS-4 and ADAMTS-5. Inhibition of the binding of ADAMTS-4 and ADAMTS-5 exosites to aggrecan should be explored as a therapeutic intervention for osteoarthritis.